Potential of Phytochemical Compounds from Natural Products as Anticancer Agents: A Systematic Literature Review - Saeful Amin; Azka Najhan; Aldy Arifin Ilham; Annisa Septiani (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Cancer is one of the leading causes of death worldwide, necessitating the development of more effective and safe anticancer therapies. Phytochemical compounds from natural sources hold great potential due to their diverse biological activities. This study aims to assess the potential of phytochemical compounds as anticancer agents through a systematic literature review of fifteen scientific articles selected based on specific inclusion criteria and analyzed qualitatively. The results indicate that compounds such as flavonoids including quercetin, polyphenols, alkaloids, and terpenoids have anticancer activity through inhibition of cell proliferation, induction of apoptosis, and inhibition of angiogenesis and metastasis, mediated by molecular pathways such as p53, nuclear factor kappa B, and caspases. In addition, approaches such as nanoformulation and combination therapy can improve the efficacy and bioavailability of the compounds. These findings indicate that phytochemical compounds have the potential to be safer and more effective anticancer agents, and require further research for clinical development